IMPLEMENTASI KEBIJAKAN SELEKSI TERBUKA DALAM PENGISIAN JABATAN PIMPINAN TINGGI PRATAMA DI LINGKUP PEMERINTAHAN KABUPATEN TORAJA UTARA - Nasir Nasir (Department of Public Administration, Muhammadiyah University of Makassar, 2019)
Open selection is carried out in order to choose the apparatus has the capacity, competence and integrity. This research aims to know the implementation of the policy of Open Selection of high Leadership Position charging Pratama in Toraja Utara. The research method used was qualitative methods. The Research Office is charging high leader pratama in the area is carried out by the conformity test, reinforcement of the mechanism and selection are open and there are three errors in the implementation of the open selection in Toraja Regency North i.e. include the Office of the Chief of administrative service of population and civil registration, passed two participants who do not qualify the maximum age and not to follow the education leadership III (three).